Perancangan Lampu Pintar Berbasis Internet of Things (IoT) Menggunakan NodeMCU Dan Blynk - Fahmi Aulia Sirait; Akim M. H. Pardede; Milli Alfhi Syari (Indonesian Journal of Education And Computer Science, 2023)
This study focuses on the design of a smart lamp adopting the Internet of Things (IoT) concept using NodeMCU and the Blynk platform. This smart lamp is designed to provide users with more flexible and convenient control through the use of the internet network. NodeMCU, a development module based on the ESP8266 microcontroller, is employed as the core of the smart lamp to connect it to the Wi-Fi network. In the design phase, the smart lamp system is implemented with the capability to be controlled through the Blynk application downloadable to the user's smartphone device. Users can control the lamp, adjust its brightness, and change the light color according to preferences through the intuitive Blynk interface. Integration with the Blynk platform allows remote access and real-time monitoring of the smart lamp's status.The test results demonstrate that the designed smart lamp can effectively communicate with the Blynk application through the Wi-Fi network. The responsive control functionality and the ability to adjust light colors and brightness provide a satisfying user experience. By combining IoT technology and the Blynk platform, this study produces a tangible example of a smart lamp implementation that enhances the convenience and comfort of managing room lighting